Frontispiz: Ein Verbindung‐I‐Analogon deckt die vorübergehende aktive Spezies eines Zytochrom‐P450‐Enzymes auf: Einblick in die Stereoselektivität P450‐katalysierter Oxidationen. (13th March 2023) - Suzuki, Kazuto; Stanfield, Joshua Kyle; Omura, Keita; Shisaka, Yuma; Ariyasu, Shinya; Kasai, Chie; Aiba, Yuichiro; Sugimoto, Hiroshi; Shoji, Osami
Abstract : Enzymes . In their Research Article (e202215706 ), Hiroshi Sugimoto, Osami Shoji et al. report the crystal structure of cytochrome P450BM3 mimicking the state of the enzyme in the moment preceding epoxidation.